Understanding police stress towards a secure and sustainable society - Bano, Bushara (International journal of police science & management, 2017)
The police is one of the most prominent organizations in a society, and police personnel are the most visible representatives of the government. They are needed at times danger, crisis and difficulty. Hence, they are expected to be the most accessible, interactive, responsive and dynamic organization in any society. Naturally, the duty and functions of police personnel are varied, multifarious and interesting. At the same time, the role of the police is complicated, elusive, problematic and complex. Primary functions of the police are mainly to prevent crime, and the maintenance of law and order. Peace and order are essential prerequisites for the development of any society and country. Thus, the police force plays a vital role in country’s development. It detects, fights, arrests and controls the enemies of peace and public order. Because of their multifarious roles, police personnel are also exposed to various stressors, which are significantly different in terms of quality and quantity compared with members of other occupational groups. This study attempts to assess stress levels among police personnel to develop a secure and sustainable society.